Evaluating the Impact of Cost on the Treatment Algorithm for Chronic Idiopathic Constipation: Cost-Effectiveness Analysis. (13th October 2021) - Shah, Eric D.; Staller, Kyle; Nee, Judy; Ahuja, Nitin K.; Chan, Walter W.; Lembo, Anthony; Brenner, Darren M.; Siegel, Corey A.; Chey, William D.
Abstract : INTRODUCTION: Chronic idiopathic constipation (CIC) is a common and burdensome illness. We performed a cost-effectiveness analysis of the US Food and Drug Administration–approved CIC drugs to evaluate and quantify treatment preferences compared with usual care from insurer and patient perspectives. METHODS: We evaluated the subset of patients with CIC and documented failure of over-the-counter (OTC) osmotic or bulk-forming laxatives. A RAND/UCLA consensus panel of 8 neurogastroenterologists informed model design. Treatment outcomes and costs were defined using integrated analyses of registered clinical trials and the US Centers for Medicare and Medicaid Services–supported cost databases. Quality-adjusted life years (QALYs) were calculated using health utilities derived from clinical trials. A 12-week time horizon was used. RESULTS: With continued OTC laxatives, CIC-related costs were 569 from an insurer perspective compared with 3, 154 from a patient perspective (considering lost wages and out-of-pocket expenses). CIC prescription drugs increased insurer costs by 618–1, 015 but decreased patient costs by 327–1, 117. Effectiveness of CIC drugs was similar (0.02 QALY gained/12 weeks or ∼7 healthy days gained/year). From an insurer perspective, prescription drugs (linaclotide, prucalopride, and plecanatide) seemed less cost-effective than continued OTC laxatives (incremental cost-effectiveness ratio >150, 000/QALY gained). From a patient perspective, the cost-effective algorithm started with plecanatide, followed by choosing between prucalopride and linaclotide starting at the 145-μg dose (favoring prucalopride among patients whose disease affects their work productivity). The patient perspective was driven by drug tolerability and treatment effects on quality of life. DISCUSSION: Addressing costs at a policy level has the potential to enable patients and clinicians to move from navigating barriers in treatment access toward truly optimizing treatment choice.